2020
DOI: 10.5114/hpr.2020.98734
|View full text |Cite
|
Sign up to set email alerts
|

The majority of professionally active women diagnosed with eating disorders may be at risk of work addiction: an overlooked comorbidity

Abstract: health psychology report •  original article background Work addiction (WA) has been previously linked to several diseases and disorders, but there is scarce literature on its association with eating disorders (EDs). Both WA and EDs share similar etiological factors (notably rigid perfectionism) and clinical features. The aim of this study was to provide an initial overview of the literature on this potential comorbidity, and investigate the co-occurrence of EDs and WA, and their relationship with sociodem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
20
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 189 publications
5
20
0
Order By: Relevance
“…Similar to work addiction, study addiction shows comorbidities with a host of other mental health problems, including substantial co-occurrences with other addictive behaviors [25,26], depression, anxiety, and social anxiety [14,24,27]. Following previous findings on the association between compulsive working and food-starving and food-binging behaviors [28][29][30], a recent study showed considerable comorbidity between work addiction and EDs [13]. This is particularly true in the case of anorexia nervosa and bulimia nervosa, where as many as five out of six women previously diagnosed with EDs fulfilled the cut-off score for work addiction.…”
Section: Introductionmentioning
confidence: 98%
See 4 more Smart Citations
“…Similar to work addiction, study addiction shows comorbidities with a host of other mental health problems, including substantial co-occurrences with other addictive behaviors [25,26], depression, anxiety, and social anxiety [14,24,27]. Following previous findings on the association between compulsive working and food-starving and food-binging behaviors [28][29][30], a recent study showed considerable comorbidity between work addiction and EDs [13]. This is particularly true in the case of anorexia nervosa and bulimia nervosa, where as many as five out of six women previously diagnosed with EDs fulfilled the cut-off score for work addiction.…”
Section: Introductionmentioning
confidence: 98%
“…While compulsive overworking is typically associated with behaviors related to professional work, eating disorders (EDs), especially anorexia nervosa (AN), are an important cause of unemployment and result in severe work impairment [11,12]. At the same time, these two classes of problematic behaviors are closely related, due to the shared risk factors (e.g., rigid perfectionism), similar clinical manifestations (e.g., excessive controlling behaviors), and consequences (e.g., physical exhaustion and depression [13]). This study aimed to examine the hypotheses that compulsive study behaviors are related to EDs, and that they have independent negative effects on well-being.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations